Low Birth Weight with Stunting Incidence for Toddlers Age 12-59 Months: Berat Badan Lahir Rendah dengan Kejadian Stunting Pada Balita Umur 12-59 Bulan - Maineny, Arie; Rifkawati; Nita Silfia, Niluh; Usman, Hastuti (Poltekkes Kemenkes Palu, 2022)
Background: The stunting tolerance level is 20% or one-fifth of the total number of children under the age of five years (WHO). Stunting was found to be more common in 24.1% of the Palu City area and 33.33% in the Nosarara Health Center. Indonesia has the highest prevalence of LBW at 11.1% after India at 27.6% and South Africa (13%). Data at the Nosarara Health Center in 2019 the incidence of LBW was 5 cases (2%), and in 2018 there were 6 cases (3%). LBW is a cause of stunting because of the difficulty of intrauterine growth when they are in the womb and will grow and develop slowly Objective: This study was to see whether there is a relationship between low birth weight (LBW) and stunting in children aged 12-59 months at the Nosarara Health Center. Methods: Case-control study with retrospective design. The study took place from 9-14 July 2020. The samples at the Nosarara Health Center were toddlers aged 12-59 months, with 33 cases and 33 controls. The sampling technique was total sampling, secondary data collection, univariate and bivariate analysis with the Chi-Square test Results: Low birth weight (LBW) showed a significant relationship with the occurrence of stunting in children aged 12-59 months. Chi-square analysis produces a p-value of 0.00010.05 Conclusion: Low birth weight (LBW) has a significant relationship with the incidence of stunting in toddlers aged 12-59 months. It is hoped that health workers will revisit the active involvement of pregnant women in monitoring health developments during pregnancy, especially maternal nutritional intake.